Critical Appraisal of C-Reactive Protein Throughout the Spectrum of Cardiovascular Disease - Osman, Raed (Dove Medical Press, 2006)
Clinicians involved in the care of patients with cardiovascular conditions have recently been confronted with an important body of literature linking inflammation and cardiovascular disease. Indeed, the level of systemic inflammation as measured by circulating levels of C-reactive protein (CRP) has been linked to prognosis in patients with atherosclerotic disease, congestive heart failure, atrial fibrillation, myocarditis, aortic valve disease and heart transplantation. In addition, a number of basic science reports suggest an active role for CRP in the pathophysiology of cardiovascular diseases. This article explores the potential role of CRP in disease initiation, progression, and clinical manifestations and reviews its role in the prediction of future events in clinical practice. Therapeutic interventions to decrease circulating levels of CRP are also reviewed.